2021
DOI: 10.1080/13102818.2021.1950566
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of soybean leaves response to manganese toxicity

Abstract: As an essential micronutrient, manganese (Mn) participates in diverse processes during plant growth and development. Excess accumulation of Mn in plants is toxic, and soybean (Glycine max) growth and production are severely limited by Mn toxicity. However, the molecular basis in adaptation to Mn toxicity for soybean remains largely unknown. In this study, RNA-seq analysis on soybean leaves was conducted, more than 44 million reads were generated, and a total of 38,022 expressed genes were identified. Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A total of 2629 and 3278 DEGs were discovered in response to Mn poisoning in grape roots of two distinct varieties, namely, Combier and Jinshou, separately, indicating that Combier and Jinshou have differing tolerances to Mn toxicity [ 54 ]. Limited genome-wide investigations have focused on leaf responses to Mn toxicity [ 2 , 55 ], but a comparison analysis of roots and leaves under Mn toxicity stress has not been carried out. In the present work, RNA-seq was used to conduct a whole genome investigation of the responding of DEGs to Mn poisoning stress on peanut roots and leaves, and 749 and 4589 DEGs were discovered from the peanut roots and leaves separately.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 2629 and 3278 DEGs were discovered in response to Mn poisoning in grape roots of two distinct varieties, namely, Combier and Jinshou, separately, indicating that Combier and Jinshou have differing tolerances to Mn toxicity [ 54 ]. Limited genome-wide investigations have focused on leaf responses to Mn toxicity [ 2 , 55 ], but a comparison analysis of roots and leaves under Mn toxicity stress has not been carried out. In the present work, RNA-seq was used to conduct a whole genome investigation of the responding of DEGs to Mn poisoning stress on peanut roots and leaves, and 749 and 4589 DEGs were discovered from the peanut roots and leaves separately.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic profiling studies revealed 731 DEGs in peanut roots suffering Mn poisoning, showing the response of peanut roots to Mn poisoning [ 8 ]. At present, genome-wide studies mainly focus on the response of soybean leaves to Mn poisoning [ 2 , 86 ]. However, no reports are available on the response of roots to Mn poisoning in soybean.…”
Section: Discussionmentioning
confidence: 99%